Themes in Plato, Aristotle, and Hellenistic Philosophy Keeling Lectures 2011-18 - Leigh, Fiona (Bulletin of the Institute of Classical Studies Supplements, 2021)
The present volume collects together papers based on the annual Keeling Memorial Lecture in ancient philosophy given at University College London, over 2011-18 (and one from 2004, previously unpublished). It contains contributions to theoretical as well as practical ancient philosophy, and in some cases, to both. Susanne Bobzien argues that Frege plagiarised the Stoics in respect of logic, Gail Fine compares uses of doxa and epistêmê in the Phaedo to contemporary notions of belief and knowledge, David Sedley offers a novel interpretation of 'safe' causal explanation in the Phaedo, and Gábor Betegh understands the ingredients of the soul in the Timaeus as structuring thought and speech. Dorothea Frede presents new considerations against a 'particularist' reading of Aristotle's ethics, Lesley Brown examines the role of agreement in establishing what is just and the correctness of names in Plato, and Gisela Striker gives an analysis of the role of Stoic therapy in the good life. A. A. Long details a new reading of divinity in the Republic that reveals the Good as the essence of the divine, and Malcolm Schofield explores the tension between unfettered theoretical debate and the demand of determinacy in practical philosophy in Cicero.